Organic chemistry. History and mutual relations of universities of Russia; Russian Journal of Organic Chemistry; Vol. 53, iss. 9 - Antipin I. S. Igor Sergeevich; Lesina Yu. A. Yuliya Aleksandrovna; Krasnokutskaya E. A . Elena Aleksandrovna; Kazymova M. A. (2017, 2017)
Title screen